2011
DOI: 10.4049/jimmunol.1002634
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Macaque Inhibitory and Activating KIR3D Interact with Mamu-A–Encoded Ligands

Abstract: Specific interactions between killer cell Ig-like receptors (KIRs) and MHC class I ligands have not been described in rhesus macaques despite their importance in biomedical research. Using KIR–Fc fusion proteins, we detected specific interactions for three inhibitory KIRs (3DLW03, 3DL05, 3DL11) and one activating KIR (3DS05). As ligands we identified Macaca mulatta MHC (Mamu)-A1– and Mamu-A3–encoded allotypes, among them Mamu-A1*001:01, which is well known for association with slow progression to AIDS in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 50 publications
2
63
0
Order By: Relevance
“…The functional implications of candidate KIR genes can already be investigated. Recently, it was reported that Mamu-KIR3DLW03, KIR3DL05, and possibly KIR3DS05 gene products can interact with Mamu-A1 Ã 001:01 and -A3 Ã 13:11 molecules [50]. Notably, these first two inhibitory genes are enriched in our animals of Chinese origin while the latter activating one is absent (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The functional implications of candidate KIR genes can already be investigated. Recently, it was reported that Mamu-KIR3DLW03, KIR3DL05, and possibly KIR3DS05 gene products can interact with Mamu-A1 Ã 001:01 and -A3 Ã 13:11 molecules [50]. Notably, these first two inhibitory genes are enriched in our animals of Chinese origin while the latter activating one is absent (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…It is evident in primates that different lineages of KIR genes have been expanded concomitantly with species‐specific evolution of MHC class I genes 216. In rhesus macaque, an important animal model of human diseases such as AIDS, binding of certain KIR is influenced by the same MHC epitopes (Bw4 and Bw6) that are important determinants of human KIR interactions 217. In the last decade, progress has been made in characterizing KIR genes in primates and developing specific genotyping assays 218, 219.…”
Section: Kir Model Systemsmentioning
confidence: 99%
“…Several candidate MHC-KIR interactions have been reported for rhesus macaques based on in vitro binding assays (Rosner et al 2011). Colantonio and colleagues made the serendipitous discovery that a recombinant soluble MHC tetramer folded around certain SIV-derived peptides could bind to the surface of lymphocytes from a subset of uninfected animals with no prior exposure to SIV or SIV antigens (Colantonio et al 2011).…”
Section: The Mhc Locus In Primate Modelsmentioning
confidence: 99%